The JEM-EUSO observation in cloudy conditions - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO (Extreme Universe Space Observatory on-board the Japanese Experiment Module) mission will conduct extensive air shower (EAS) observations on the International Space Station (ISS). Following the ISS orbit, JEM-EUSO will experience continuous changes in the atmospheric conditions, including cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate from both EAS property and cloud climatology points of view. In the present work, the impact of clouds on the apparent profile of EAS is demonstrated through the simulation studies, taking into account the JEM-EUSO instrument and properties of the clouds. These results show a dependence on the cloud-top altitude and optical depth of the cloud. The analyses of satellite measurements on the cloud distribution indicate that more than 60 % of the cases allow for conventional EAS observation, and an additional similar to 20 % with reduced quality. The combination of the relevant factors results in an effective trigger aperture of EAS observation similar to 72 %, compared to the one in the clear atmosphere condition.
Keywords: JEM-EUSO; Ultra-high energy cosmic ray; Extensive air shower